Pemanfaatan Media Sosial dalam Melestarikan Budaya Lokal Bangka Belitung - Laila Hayati; Putra Pratama Saputra; Yulia Yulia; Tiara Ramadhani (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The advanced of information technology has facilitated society to interact each other without border of the time and space. It transforms into platform known as social media. The social media becomes a potential platform to assimilate the western culture into the local culture. It threats the local identity. The program aims to maintain the local culture of Bangka Belitung Islands Province by utilizing the social media. Thus, the training on utilizing the social media in maintaining the local culture of the province into the active users among the students in SMA N 1 Sungai Selan, SMA N 1 Air Gegas, and SMA N 1 Kelapa was used as the method of the community service. The program found that the participants showed their enthusiastic in maintaining their culture by using social media. 70 percent of the participants had utilized the social media in maintaining the local culture by uploading text, picture, and video on their social media account.